TENDENCIES OF INNOVATIVE MANAGEMENT OF KAZAKHSTAN - Kairatova, G.; Myltykbaeva, A. (Journal of Economic Research & Business Administration, 2017)
In this article the formation and development of innovation processes in the Republic of Kazakhstan, as the introduction of innovations and their effective use, promote the competitiveness of the national economy and economic development of the country. The innovative activity of the Republic of Kazakhstan, based on the introduction of new ideas, scientific knowledge, technologies and types of products in various fields of production and the sphere of society management, is one of the most important factors for the development of the republic’s economy. The need to create in the future a competitive innovative economy in the Republic of Kazakhstan. To improve the economy of the country in the future, the Kazakhstan-2050 Strategy proclaims a policy of diversifying the economy, developing industries with high surplus value, and an accelerated industrial-innovative development has been approved to achieve this. Resource opportunities and technological potential, as well as financial means for modernization of the country.